Post-licensure safety monitoring of quadrivalent human papillomavirus vaccine using the national adverse event following immunization surveillance system from Zhejiang province, 2018-2020 - Yu Hu; Xuejiao Pan; Linzhi Shen; Fuxing Chen; Ying Wang; Hui Liang; Yaping Chen; Huakun Lv (Taylor & Francis Group, 2021)
Objectives To evaluate the reporting rate of adverse events following immunization (AEFI) of the quadrivalent human papillomavirus vaccine (4vHPV) and to compare the reporting rate of AEFI following 4vHPV with those following other vaccines. Methods Review and describe the AEFI reported to national adverse event following immunization surveillance system (NAEFISS) in Zhejiang province from 2018 to 2020. Reporting rates of AEFI were calculated by age, city, severity of AEFI, categories of AEFI, and reaction categories. The data mining algorithm used in this study was reporting odds ratio (ROR). A value of ROR‑1.96SE >1 (standard error [SE]) was considered as positive signal. Results NAEFISS received 238 reports after receipt of 4vHPV and 899,282 doses of 4vHPV were administered during the study period, with a crude reporting rate of 2.7/10000 doses. Fever/redness/induration (101 reports) was the most common event reported (1.12/10000 doses). Two cases of anaphylactic shock, three cases of Guillain Barre Syndrome and two cases of acute disseminated encephalomyelitis were reported. ROR showed positive signals for seizure (ROR‑1.96SE: 2.1), syncope (ROR‑1.96SE: 1.3), allergic rash (ROR‑1.96SE: 1.6) and headache (ROR‑1.96SE: 2.1). Conclusion The present analysis did not identify new/unexpected safety concerns. Further epidemiological studies are required to systematically validate the data provided by NAEFISS.